Differential defence responses expressed in mango (Mangifera indica) cultivars against Colletotrichum gloeosporioides - and C.L. ABAYASEKARA, G.D. SINNIAH, N.K.B. ADIKARAM* (Indian Phytopathology, 2013)
This paper reports evidence that unripe mango fruit responds to Colletotrichum gloeosporioides, the anthracnose pathogen, by inducing several defence mechanisms. Localized generation of superoxide (O2-) and hydrogen peroxide (H2O2) was observed within hours in the pathogen-challenged epidermal cells, as early defence responses. O2 - production was greater in the cultivar ‘Karutha Colomban’ more resistant to anthracnose than the susceptible ‘Willard’. O2 - production was also greater in C. gloeosporioides inoculated unripe fruits than in inoculated ripe fruits of both cultivars. Autofluorescence was first observed in challenged epidermal cells, 12 h after inoculation indicating hypersensitive response. Increased phenylalanine ammonia-lyase (PAL) activity and accumulation of lignin were observed in the infected peel. There was enhanced chitinase activity in the inoculated peel tissue probably resulting from induced chitinase isoforms with 59.4 kDa and 44.5 kDa molecular weight. In general, the early induced defence responses were more prominent in the resistant than in the susceptible cultivar. In both cultivars C. gloeosporioides becomes quiescent, due to the presence of constitutive antifungal substances in the fruit peel which decline during ripening. Greater resistance induced in the resistant cultivar, `Karutha Colomban’ may be restricting C. gloeosporioides development in the ripe fruits, reducing anthracnose disease. Outcome of this study sheds a new insight into the natural disease resistance of mango against C. gloeosporioides.